Analysis of reactive multi-branch relaying under interference and Nakagami-m fading - Forghani, Amir; Aissa, S.; Xia, M. (2017)
© 2017 IEEE. The performance of reactive decode-and-forward multi-branch relaying in the presence of co-channel interference and Nakagami fading is analytically investigated. Intermediate relays that successfully decode the received signals from the source node form a decoding set, from which the relay whose corresponding branch results in the highest signal-to-interference-plus-noise ratio (SINR) at the destination node is chosen to serve as the best relay. The selected relay re-encodes the source message and forwards it to the destination while the remaining relays keep idle. For this relaying scheme, we first obtain the exact end-to-end SINR expression by considering the general case of Nakagami-m fading channels. Then, the exact unconditional probability density function (PDF) of the end-to-end SINR is explicitly derived. With the resulting PDF, exact closed-form expressions for the outage and error probabilities are obtained. Moreover, to gain insights into the system performance, asymptotic analysis of the error probability is performed. Finally, Monte-Carlo simulation results are presented to corroborate the analysis, and comparative numerical results are discussed.